Adherence to Governance Patterns: How Do Institutional Work and Knowledge Dissemination Influence the Institutionalization of Brazilian Industrial Clusters? - Jacometti, Márcio; Aparecido Gonçalves, Sandro; Bonfim, Leandro; César de Oliveira, Luiz (Review of Business Management, 2024)
Purpose – This article examines how the institutional work of inducing agents and the dissemination of knowledge among induced immersed actors have influenced adherence to governance standards in Brazilian industrial clusters. Theoretical framework – We use institutional theory to frame the relationships between embedded firms through regulatory, normative, and cultural-cognitive pillars and the view of field-level agents engaged in institutional work, who share knowledge to induce adherence to governance standards. Design/methodology/approach – We adopted a mixed methods research design, examining 96 companies in three Brazilian industrial clusters. We used WABA analysis to test our model within and between clusters using one-way ANOVA tests, and we tested our hypotheses using correlations identified in t-tests between independent samples and multiple linear regression to build the model. Findings – The findings reveal that institutional work affects the dissemination of knowledge at multiple levels, influencing companies' adherence to cluster governance standards. We show that less adherence to new governance standards can be explained by the lack of internalization of disseminated knowledge. The institutional structures that historically existed before the implementation of formal governance prevail over the new ones, since the knowledge disseminated in these clusters tends to maintain current economic and institutional conditions, with little support for the creation of new institutions. Practical & social implications of research – Cognitive aspects of the internalization of explicit, effective, and institutional knowledge suggest that its dissemination influences firms’ adherence to the industrial cluster’s governance patterns. Originality/value – Little attention has been paid to how knowledge dissemination and institutional work can lead to the creation of and adherence to industrial cluster governance standards; and the dissemination of knowledge is more effective when social relations are included in the analysis model. Keywords – Institutional work. Knowledge dissemination. Industrial clusters. Governance patterns. Microfoundations of institutionalization.